CCL19 with CCL21‐tail displays enhanced glycosaminoglycan binding with retained chemotactic potency in dendritic cells. Issue 2 (16th May 2018) - Jørgensen, Astrid S.; Adogamhe, Pontian E.; Laufer, Julia M.; Legler, Daniel F.; Veldkamp, Christopher T.; Rosenkilde, Mette M.; Hjortø, Gertrud M.
Abstract: CCL19 is more potent than CCL21 in inducing chemotaxis of human dendritic cells (DC). This difference is attributed to 1) a stronger interaction of the basic C‐terminal tail of CCL21 with acidic glycosaminoglycans (GAGs) in the environment and 2) an autoinhibitory function of this C‐terminal tail. Moreover, different receptor docking modes and tissue expression patterns of CCL19 and CCL21 contribute to fine‐tuned control of CCR7 signaling. Here, we investigate the effect of the tail of CCL21 on chemokine binding to GAGs and on CCR7 activation. We show that transfer of CCL21‐tail to CCL19 (CCL19 CCL21‐tail ) markedly increases binding of CCL19 to human dendritic cell surfaces, without impairing CCL19‐induced intracellular calcium release or DC chemotaxis, although it causes reduced CCR7 internalization. The more potent chemotaxis induced by CCL19 and CCL19 CCL21‐tail compared to CCL21 is not transferred to CCL21 by replacing its N‐terminus with that of CCL19 (CCL21 CCL19‐N‐term ). Measurements of cAMP production in CHO cells uncover that CCL21‐tail transfer (CCL19 CCL21‐tail ) negatively affects CCL19 potency, whereas removal of CCL21‐tail (CCL21 tailless ) increases signaling compared to full‐length CCL21, indicating that the tail negatively affects signaling via cAMP. Similar to chemokine‐driven calcium mobilization and chemotaxis, the potency of CCL21 in cAMP is not improved by transfer of the CCL19 N‐terminus to CCL21 (CCL21 CCL19‐N‐term ). Together these results indicate that ligands containing CCL21 core and C‐terminal tail (CCL21 and CCL21 CCL19‐N‐term ) are most restricted in their cAMP signaling; a phenotype attributed to a stronger GAG binding of CCL21 and defined structural differences between CCL19 and CCL21. Abstract : Low chemotaxis potency of CCL21 relies on overall chemokine structure since it cannot be transferred by tail alone.